2014
DOI: 10.2967/jnumed.114.144055
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Uptake Characterization Through Texture Analysis: Investigating the Complementary Nature of Heterogeneity and Functional Tumor Volume in a Multi–Cancer Site Patient Cohort

Abstract: Intratumoral uptake heterogeneity in 18 F-FDG PET has been associated with patient treatment outcomes in several cancer types. Textural feature analysis is a promising method for its quantification. An open issue associated with textural features for the quantification of intratumoral heterogeneity concerns its added contribution and dependence on the metabolically active tumor volume (MATV), which has already been shown to be a significant predictive and prognostic parameter. Our objective was to address this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
386
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(420 citation statements)
references
References 21 publications
25
386
0
9
Order By: Relevance
“…As a result of this initiative, first reports have appeared that point at promising results of a quantitative assessment of tumor heterogeneity in light of therapy response prediction [270,271], disease-specific survival [272] as well as prognostic stratification [273]. Meanwhile, challenges using textural features remain, since such calculations are highly sensitive to acquisition, reconstruction and sample size variations [274][275][276]. Overall, the need of reproducibility evaluation as well as standardization of textural features is being acknowledged in the field [274].…”
Section: In Vivo Disease Characterizationmentioning
confidence: 99%
“…As a result of this initiative, first reports have appeared that point at promising results of a quantitative assessment of tumor heterogeneity in light of therapy response prediction [270,271], disease-specific survival [272] as well as prognostic stratification [273]. Meanwhile, challenges using textural features remain, since such calculations are highly sensitive to acquisition, reconstruction and sample size variations [274][275][276]. Overall, the need of reproducibility evaluation as well as standardization of textural features is being acknowledged in the field [274].…”
Section: In Vivo Disease Characterizationmentioning
confidence: 99%
“…We believe this to be the largest study performed for esophageal cancer and believe that our results are robust-whether they can be extrapolated to NACR is not clear, but we believe these results warrant urgent assessment. In addition, assessment of several textural response parameters, including entropy and run-length matrices, which although not routinely used in clinical practice have recently been shown to be associated with pTR after NACR (44), and their inclusion in conjunction with volume have been suggested to improve prognostication (45). Such metrics may therefore provide complementary predictive data.…”
Section: Discussionmentioning
confidence: 99%
“…One team showed that textural analysis of baseline CT images are correlated to progression-free survival and can be combined with information from interim-PET [30]. There also is potential for textural analysis of baseline PET images to yield useful information [31,32]. Numerous biomarkers within the Reed-Sternberg cell and its microenvironment can also be exploited [33].…”
mentioning
confidence: 99%